Ben Boyd of Boydtown - Diamond, Marion, 1948- (Carlton, Vic. : Melbourne University Press, 1995)
Sydney was agog when, in 1842, Ben Boyd's Wanderer, an aristocratic racing yacht from the Royal Yacht Squadron, swept into the Harbour. Boyd was chairman of the Royal Bank of Australia, which he founded in London. He had the blessing of the Colonial Office, and the security of friends in high places. He was about to become the bank's largest customer. Boyd soon became the biggest of all the squatters in New South Wales and one of the largest employers. He helped to destroy one governor, become creditor of another, and threatened the New Zealand government with bankruptcy. Then, after just seven years, he fled - his personal credit and financial empire destroyed and the Royal Bank facing receivership.
What became of this intrepid merchant adventurer? The denouement - revenge in the 'cannibal islands' he had exploited - is the stuff of romantic fiction; but a ruined lighthouse at Boydtown grounds this story firmly in our history. Now for the first time, Marion Diamond reveals the murky details of his bloody death.
Originally published: The Sea Horse and the Wanderer. 1988.
Includes bibliographical references (p. 240-246) and index.
Keywords: Boyd, Benjamin, -- 1803?-1851.; Pioneers -- New South Wales -- Biography; Businessmen -- New South Wales -- Biography; Capitalists and financiers -- New South Wales -- Biography; New South Wales -- Biography